Plasma chromium levels in small-for-gestational-age newborn infants - Yurdakök, Murat; Özer, Durişehvar; Erdem, Gülşen; Temizer, Aytekin (The Turkish Journal of Pediatrics, 1993)
Plasma chromium (Cr) levels were determined in 24 preterms and 18 full-term newborn infants. There was no statistically significant differences in plasma Cr levels between the preterm and full-term infants. Plasma Cr levels were similar in small-for-gestational-age infants and in infants with hypoglycemia compared with healthy infants.